2019
DOI: 10.3389/fimmu.2019.00914
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid Attenuation of Intestinal Inflammation in Chronic SIV-Infected Rhesus Macaques Involves T Cell Modulation and Differential Expression of Micro-RNAs and Pro-inflammatory Genes

Abstract: Cannabis use is frequent in HIV-infected individuals for its appetite stimulation and anti-inflammatory effects. To identify the underlying molecular mechanisms associated with these effects, we simultaneously profiled micro-RNA (miRNA) and mRNA expression in the colon of chronically simian immunodeficiency virus (SIV)-infected rhesus macaques administered either vehicle (VEH/SIV; n = 9) or Δ 9 -tetrahydrocannabinol (Δ 9 -THC; THC/SIV; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
80
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(84 citation statements)
references
References 62 publications
(121 reference statements)
4
80
0
Order By: Relevance
“…Numerous studies, including studies from our group [ 8 , 9 , 10 , 11 , 12 ], showed that administration of THC is linked to a beneficial reduction in systemic inflammation and immune activation in ART-treated HIV+ individuals. In the SIV/rhesus macaque model, THC was shown to ameliorate SIV disease progression [ 24 , 25 ], reduce intestinal T cell activation/exhaustion and prevent lymph node fibrosis [ 10 ]. The benefits of THC are systemic, affect many organs, and are also present in BEVs, which may mediate THC action, as shown by the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Numerous studies, including studies from our group [ 8 , 9 , 10 , 11 , 12 ], showed that administration of THC is linked to a beneficial reduction in systemic inflammation and immune activation in ART-treated HIV+ individuals. In the SIV/rhesus macaque model, THC was shown to ameliorate SIV disease progression [ 24 , 25 ], reduce intestinal T cell activation/exhaustion and prevent lymph node fibrosis [ 10 ]. The benefits of THC are systemic, affect many organs, and are also present in BEVs, which may mediate THC action, as shown by the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The optimization of the THC dosing in rhesus macaques accounts for the development of tolerance during the initial period of administration. Because this dose of THC showed protection in our previously published studies [ 10 ], the same dose was used in this study. SIV levels in plasma were quantified by using the TaqMan One-Step Real-Time RT-qPCR assay that targeted the long terminal repeats (LTRs) gene [ 10 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Infl ammation-induced improvements in vascular permeability result in the accumulation of more fl uid in endothelial cells than can be absorbed. 8 In previously studies on cannabinoid (CB) agonists, they have been found to reduce the antinociceptive and anti-infl ammatory eff ects of CB agonists. 3,9,10 In particular, they have been found to mediate the eff ects of antiedema and anti-infl ammatory through peripheral CB2 receptors.…”
Section: Introductionmentioning
confidence: 99%